2019
DOI: 10.1123/ijspp.2018-0151
|View full text |Cite
|
Sign up to set email alerts
|

Running Economy: Neuromuscular and Joint-Stiffness Contributions in Trained Runners

Abstract: Greater muscle pre-activation and bi-articular muscle activity during stance were associated with more economical runners. Consequently, trained runners who exhibit greater neuromuscular activation prior to and during ground contact, in turn optimise spatiotemporal variables and joint stiffness, will be the most economical runners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 32 publications
3
56
0
3
Order By: Relevance
“…Specifically, greater medial gastrocnemius and lower tibialis anterior activation were associated with favourable race walking economy. A similar finding has been previously observed in runners at 12 km•h -1 although this was over the entire ground contact phase 18 . This study further details the temporal nature of this relationship that was found between 5-8% of the gait cycle in the medial gastrocnemius and 6-12% of the gait cycle in the tibialis anterior.…”
Section: Midstancesupporting
confidence: 90%
See 2 more Smart Citations
“…Specifically, greater medial gastrocnemius and lower tibialis anterior activation were associated with favourable race walking economy. A similar finding has been previously observed in runners at 12 km•h -1 although this was over the entire ground contact phase 18 . This study further details the temporal nature of this relationship that was found between 5-8% of the gait cycle in the medial gastrocnemius and 6-12% of the gait cycle in the tibialis anterior.…”
Section: Midstancesupporting
confidence: 90%
“…Large loading forces are experienced at initial ground contact, and the management of these forces is key to efficient energy transfer and reduced metabolic demand during ground contact 25 . Mechanisms to facilitate these forces appear to be associated with pre-activation 19 during terminal swing 16 and consequent joint biomechanics that enable efficient gait 18 . Thus, during initial ground contact, the biarticular muscle, biceps femoris appears to behave as a joint stabiliser for both the knee and hip, as similar findings have been found previously during running by Moore et al 26 and Heise et al 17 .…”
Section: Terminal Swing and Initial Ground Contactmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the biomechanical load will be distributed differently and hence load other tissues that may not be adapted to this load, thereby increasing injury risk. Changing from a heel strike to a forefoot strike, for example, increases plantar flexors and Achilles tendon forces, which may lead to plantar flexor strains and Achilles tendinopathy (Barnes et al, 2014;Folland et al, 2017;Gomez-Molina et al, 2017;Pizzuto et al, 2019;Santos-Concejero et al, 2013;Santos-Concejero et al, 2015;Santos-Concejero et al, 2017;Santos-Concejero et al, 2014b;Støren et al, 2011;Tam et al, 2018;Tartaruga et al, 2012;Tartaruga et al, 2009;Williams & Cavanagh, 1987)…”
Section: How To Modify Running Technique?mentioning
confidence: 99%
“…Considerando a capacidade do alongamento de interferir no desempenho da corrida de longas distâncias, e que existem características biomecânicas da corrida que podem contribuir para um melhor desempenho na corrida (ABE et al, 2007;ANDERSON, 1996;KILDING, 2015;MARTIN, 2001;LACOUR;BOURDIN, 2015;MOORE, 2016;SAUNDERS et al, 2004;TAM et al, 2017TAM et al, , 2018, entender o comportamento biomecânico da corrida em função desse estímulo pode contribuir no esforço de elucidar as adaptações do corpo humano ao alongamento.…”
Section: Lista De Figurasunclassified